KM Maturity for A Gas Company in Indonesia: G-KMMM Assessment and Improvement Recommendation - Handoko Ramadhan; Majesty Permana; Dana I. Sensuse; Sofian Lusa; Damayanti Elisabeth (Proceeding of the Electrical Engineering Computer Science and Informatics, 2020)
Knowledge is an intellectual asset owned by each organization that greatly influences the performance of the organization. Knowledge management, tacit knowledge, and explicit knowledge in an organization become crucial for the organization's sustainability. The governance depends on many things such as organizational structure, human resources and culture, technology, and the company's vision and mission. In order to adjust between company objectives, it is necessary to know the KM maturity index in an organization. So based on the maturity index, the organization can prepare and adjust company conditions based on the target to be achieved. Knowledge Management (KM) has helped many companies or organizations in developing companies or their organizations, especially for the oil and gas industry. In this study, the authors used the G-KMMM method to conduct KM assessments and provide recommendations for increasing KM at an oil and gas company in Indonesia. From the KM assessment results using the G-KMMM method, it was found that KM in that company is at the awareness level. These results are obtained by considering aspects of people, processes, and technology.